Palliative care education and training in Liberia: A qualitative exploration of current state and challenges to further development - Moses Tende Stephens; Erna Rochmawati (Belitung Raya Foundation, Indonesia, 2022)
Background: Palliative care is an integral approach to enhancing patients’ overall quality of life by taking into account their entire lives and addressing any suffering they may be experiencing. Thus, palliative care education and training should be advanced. However, palliative care training and education in Liberia have just started, and their development warrants further investigation. Objective: This research aimed to explore the state of palliative care education in Liberia and highlight its barriers and challenges. Methods: A descriptive qualitative exploratory study design was adopted in this study. Semi-structured interviews were conducted with ten male lecturers and four female nurses to gain in‐depth insight into their perspectives on palliative care education. Thematic analysis with NVivo 12 plus was used for data analysis. Results: Four themes emerged from the data: 1) the need for palliative education (lack of healthcare professionals, government support, regular workshops, integration, and interprofessional education on palliative care), 2) palliative care barriers (lack of curriculum implementation, lack of experience, lack of government actions, and poor infrastructures), 3) the level of student knowledge (senior and junior level, same educational level, and regular teaching materials), and 4) the roles of health care professionals (attention on palliative care, providing education on pain, and public awareness). Conclusion: The study findings may serve as input to develop palliative care education and training in Liberia. The identified gaps must be filled, and critical barriers must be overcome if the area of palliative care needs to be advanced. However, the comprehensive knowledge gathered in this study can be used by nurses, lecturers, and multidisciplinary teams to achieve the effectiveness of palliative care for patients.